A molecular phylogeny and revision of the genus Pyropteron Newman, 1832 (Lepidoptera, Sesiidae) reveals unexpected diversity and frequent hostplant switch as a driver of speciation - Bartsch, Daniel; Pühringer, Franz; Milla, Liz; Lingenhöle, Arthur; Kallies, Axel (Zootaxa, 2021)
We here revise the genus Pyropteron Newman, 1832 using molecular and morphological analyses. Our data support the monophyly of Pyropteron with Synansphecia Căpușe, 1973 (syn. rev.) being its junior subjective synonym. Four taxa are described as new to science, Pyropteron minianiformis xerxes Bartsch, Pühringer, Lingenhöle & Kallies ssp. nov., Pyropteron hellenicum Bartsch, Pühringer, Lingenhöle & Kallies sp. nov., Pyropteron jordanicum Bartsch, Pühringer, Lingenhöle & Kallies sp. nov. and Pyropteron leucomelaena blaesii Bartsch, Pühringer, Lingenhöle & Kallies ssp. nov., and 4 species are raised to species rank, Pyropteron nigrobarbata (Rebel, 1916) stat. nov., Pyropteron icteropus (Zeller, 1847) stat. rev., Pyropteron euglossaeformis (Lucas, 1849) stat. rev. and Pyropteron erodiiphaga (Dumont, 1922) stat. rev. To stabilize the taxonomy, we designate neotypes for Pyropteron euglossaeformis stat. rev. and Pyropteron ceriaeformis (Lucas, 1849). Pyropteron pipiziformis (Lederer, 1855) comb. nov., is combined with Pyropteron for the first time. The identity of Pyropteron atlantis (Schwingenschuss, 1935), previously confused with Pyropteron borreyi (Le Cerf, 1922) is fixed. We treat Pyropteron muscaeformis lusohispanica Laštůvka & Laštůvka, 2007 syn. nov. as a synonym of Pyropteron koschwitzi (Špatenka, 1992), Pyropteron minianiformis aphrodite Bartsch, 2004 syn. nov. as a synonym of Pyropteron minianiformis destituta (Staudinger, 1894), Pyropteron muscaeformis occidentalis Joannis, 1908 syn. nov. as a synonym of Pyropteron muscaeformis (Esper, 1783), and Sesia lecerfi Oberthür, 1909 syn. nov. is considered a synonym of Bembecia ichneumoniformis ([Denis & Schiffermüller], 1775). Finally, we discuss a model whereby frequent switches in hostplant usage drive rapid speciation in the genus Pyropteron.